2016
DOI: 10.1002/lary.25980
|View full text |Cite
|
Sign up to set email alerts
|

A prospective cohort study of the silk fibroin patch in chronic tympanic membrane perforation

Abstract: 2b Laryngoscope, 126:2798-2803, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 23 publications
(53 reference statements)
0
20
0
Order By: Relevance
“…Thin silk films have also been used in prospective human clinical trials to repair acute and chornic tympanic membrane perforations . These silk patches (Tympasil, Daewoong‐Bio, Seoul, South Korea) were generated using reverse engineered Bombyx mori silk fibroin.…”
Section: Clinical Trials Using Silkmentioning
confidence: 99%
See 2 more Smart Citations
“…Thin silk films have also been used in prospective human clinical trials to repair acute and chornic tympanic membrane perforations . These silk patches (Tympasil, Daewoong‐Bio, Seoul, South Korea) were generated using reverse engineered Bombyx mori silk fibroin.…”
Section: Clinical Trials Using Silkmentioning
confidence: 99%
“…The first clinical trial involved 52 patients with acute traumatic tympanic membrane perforation who were treated with either a silk film or a paper‐based membrane. [115b] A number of conservative treatment modalities had been explored to support the (often spontaneous) healing of an acutely perforated tympanic membrane, including the placement of a “patch” on top of the damaged tympanic membrane. In this trial, the silk or paper patches were surgically placed and removed 7 days later, when the tympanic membrane appeared fully regenerated.…”
Section: Clinical Trials Using Silkmentioning
confidence: 99%
See 1 more Smart Citation
“…Because we assured the advantage of synthetic biocomportable patch in this study, silk patch was tried in the other prospective cohort study: comparative analysis between silk patch and conventional perichondrial myringoplasty in chronic tympanic membrane perforation [6]. With these two clinical reports [6,7], we carefully suggested that the silk patch has advantage effect on healing process of perforated tympanic membrane even though acute or chronic condition.…”
mentioning
confidence: 99%
“…With these two clinical reports [6,7], we carefully suggested that the silk patch has advantage effect on healing process of perforated tympanic membrane even though acute or chronic condition.…”
mentioning
confidence: 99%